THE RECONSTRUCTING LEGAL POLICIES OF THE MANAGEMENT AND CONTROL OF ENVIRONMENTAL IMPACTS FOR INDUSTRIAL AREAS IN URBAN OF CENTRAL JAVA - Widodo, Agus; Hossain, Mohammad Belayet (International Journal of Law Reconstruction, 2022)
The pace of development is often faced with the challenge of decreasing the quality of a healthy environment. Meanwhile, the management and control of impacts must continue to be pursued properly and committed to maintaining health and environmental sustainability. This article aims to describe how environmental management in the city of Semarang is amid the rapid industrial growth in the area and what obstacles and challenges are faced. This study uses an empirical juridical approach with qualitative analysis techniques. The study results indicate that the strategy for controlling environmental impacts includes developing priority programs and strategies. The program can be measured in a certain time with clear benchmarks of success, structuring regulations in the field of pollution control, increasing the commitment of decision-makers in government and society, and community participation in environmental impact control programs. On the other hand, the function of Central Java’s Environmental Impact Control Agency (Bapedalda) is to monitor the implementation of Environmental Feasibility Study (EFS), evaluate environmental impact control activities and EFS implementation in the region, provide recommendations for determining EFS approval, make efforts to inform EFS, carry out technical guidance and supervision of environmental impact control, restore the environmental quality of life and control pollution and environmental damage.